Therapeutic Potential of Moringa oleifera Leaves in Chronic Hyperglycemia and Dyslipidemia: A Review - Mbikay, Majambu (Frontiers in Pharmacology, 2012)
Moringa oleifera (M. oleifera) is an angiosperm plant, native of the Indian subcontinent, where its various parts have been utilized throughout history as food and medicine. It is now cultivated in all tropical and subtropical regions of the world. The nutritional, prophylactic, and therapeutic virtues of this plant are being extolled on the Internet. Dietary consumption of its part is therein promoted as a strategy of personal health preservation and self-medication in various diseases. The enthusiasm for the health benefits of M. oleifera is in dire contrast with the scarcity of strong experimental and clinical evidence supporting them. Fortunately, the chasm is slowly being filled. In this article, I review current scientific data on the corrective potential of M. oleifera leaves in chronic hyperglycemia and dyslipidemia, as symptoms of diabetes and cardiovascular disease risk. Reported studies in experimental animals and humans, although limited in number and variable in design, seem concordant in their support for this potential. However, before M. oleifera leaf formulations can be recommended as medication in the prevention or treatment of diabetes and cardiovascular disease, it is necessary that the scientific basis of their efficacy, the therapeutic modalities of their administration and their possible side effects be more rigorously determined.